2000
DOI: 10.1042/ba20000014
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing effect of chemical additives against oxidation of lactate dehydrogenase

Abstract: Oxidation is one of the major pathways for denaturation of proteins during storage, and also a potential problem in protein production, isolation and purification processes. In this study, a number of additives have been tested for their protective effects against oxidation in the presence of metal ions and hydrogen peroxide. Porcine muscle lactate dehydrogenase (LDH) was used as a model protein. Oxidation and denaturation of the enzyme were followed as activity loss, modification of certain amino acids, alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 36 publications
2
48
0
1
Order By: Relevance
“…In silico analysis of the Ϫ10 and Ϫ35 sequences of these regions showed that ectAp1 and ectAp2 may be dependent on the main vegetative factor 70 , whereas ectAp3 and ectBp were similar to S -and 32 -dependent promoters, respectively. In agreement with these predictions, expression of an ectAp (1)(2)(3)(4)::lacZ fusion was osmoregulated and depended in part on the general stress factor S , whereas ectBp was induced by continuous growth at a high temperature. Very interestingly, expression from ectAp was reduced when excess iron (50 M FeCl 3 ) was added to the medium, suggesting that there is a regulatory link between iron homeostasis and the osmostress response in C. salexigens (11).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…In silico analysis of the Ϫ10 and Ϫ35 sequences of these regions showed that ectAp1 and ectAp2 may be dependent on the main vegetative factor 70 , whereas ectAp3 and ectBp were similar to S -and 32 -dependent promoters, respectively. In agreement with these predictions, expression of an ectAp (1)(2)(3)(4)::lacZ fusion was osmoregulated and depended in part on the general stress factor S , whereas ectBp was induced by continuous growth at a high temperature. Very interestingly, expression from ectAp was reduced when excess iron (50 M FeCl 3 ) was added to the medium, suggesting that there is a regulatory link between iron homeostasis and the osmostress response in C. salexigens (11).…”
supporting
confidence: 66%
“…Hydroxyectoine was able to protect lactate dehydrogenase from metal-catalyzed oxidation (2) and to protect plasmid DNA from damage by a number of OH radical-producing systems, including 0.1 mM FeCl 3 (45). Therefore, our interpretation is that this is a way for C. salexigens to respond to the oxidative stress imposed by excess iron (50 M FeCl 3 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Porcine muscle lactate dehydrogenase was submitted to oxidation in the presence of metal ions and hydrogen peroxide, in the presence of a variety of compounds [211]. The best protecting agent was found to be the poly(ethyleneimine), followed by EDTA.…”
Section: Keeping Hydrogen Peroxide Concentration At Low Levelsmentioning
confidence: 99%
“…Hydroxyectoine has previously been reported to modestly improve survival of freeze-dried E. coli (23). It can also protect susceptible enzymes against desiccation and other stresses in vitro (1,22), although other authors have shown that hydroxyectoine inhibits certain enzyme activities and DNA-protein complex formation (25), implying a potentially negative impact on metabolism.…”
Section: Discussionmentioning
confidence: 99%